RELATIONSHIP OF TOTAL SUSPENDED SOLID (TSS) WITH PHYTOPLANKTON ABUNDANCE IN PADANG STRAIT WATERS OF BENGKALIS REGENCY RIAU PROVINCE - Ardian Dwi Pratama; Sofyan Husein Siregar; Mubarak Mubarak (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This research was conducted in March to April 2019. The purpose of this research was to find out value of total suspended solid (TSS) content,value of phytoplankton abundance, and the relationship between the total suspended solid (TSS) and the abundance of phytoplankton. This research used survey method, there is arefour sampling stations with three replications in each station. The results showed, that the highest average of TSS contentin Padang Strait waters was found in Station 3 (241,33 mg/l) and the lowest in Station 4 (193,33 mg/l). The types of phytoplankton was found in Padang Strait waters was 14 types, they areBacillaria sp, Closterium sp, Coscinodiscus sp, Isthmia sp, Rhizosolenia sp, Synedra sp, Navicula sp, Skeletonema sp, Thalassionema sp, Oscillatoria sp, Nitzschia sp, Hantzschia sp, Amphora sp, and Pleurosigma sp with the most dominant types are Isthmia sp and Rhizosolenia sp. The highest abundance was found in aroundMangrove Area of Pangkalan Jambi Village (3247,59 ind/l) and the lowest was found inSungai Selari Port (1538,18 ind/l).Based on simple linear regression, the relationship ofTSS content with phytoplankton abundance showed a intense negative relationship, it means that the increasing of TSS content will decreasing abundance of phytoplankton in Padang Strait waters. Keywords:Padang Strait, TSS, Abundance of Phytoplankton